Research on the influence of technological factors on the quality indicators of cement-lime plaster Siltek RM-10 - BASARAB, Volodymyr; HLUSHCHENKO, Iryna; UMANETS, Iryna; STOYAN , Alexander (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the study of the influence of technological factors on the quality indicators of the installation of cement-lime plaster Siltek PM-10. Technological factors varied at the following levels: X1 – concentration of surface priming with Siltek E-100 primer – 50±50%; X2 – surface humidity – 1.4±0.8%; X3 – mobility of the mortar mixture – 8±1 cm. The processing of the experimental results was performed in the COMPEX-99 ODABA software package. The normalized indicators of Siltek PM-10 cement-lime plaster at a 28-day age were taken to be compressive strength of more than 2.5 MPa, tensile strength when bending of more than 1.2 MPa, and adhesion strength to the base of more than 0.3 MPa. The adhesion strength of the plaster surface of 0.3 MPa was obtained at a humidity of 2.2% with a mobility of the mortar mixture of 8 cm at the studied concentrations of the primer. When the humidity of the base is 0.6% with a mobility of the mortar mixture of 8 cm, the required values of adhesion strength are achieved with priming from 0% to 11.6% and from 87.5% to 100%. Satisfactory adhesion to surfaces made of expanded clay concrete blocks with a mortar mobility of 8 cm was obtained in the absence of priming and with a primer concentration of 100% with a humidity of 0.6% to 0.84% and from 1.68 to 2.2 or with a primer concentration of 50% with a humidity of 2.12% to 2.2%. Accordingly, with a mobility of the mortar mixture of 7 cm on bases with a primer concentration of 0% and 100%, the necessary adhesion is achieved on surfaces with a humidity of 1.47% to 2.2%, and if the primer concentration is 50%, then the humidity is from 2.07% to 2.2%. For a mobility of 9 cm on expanded clay concrete surfaces with a primer concentration of 0% and 100%, the bond strength is more than 0.3 MPa on surfaces with a humidity of 1.38% to 2.2%, and if the primer concentration is 50%, then the humidity is from 1.9% to 2.2%.